Fungsi Lembaga Adat Dalam Pembangunan Desa Tengku Lawar Dan Desa Lamba Keli Kecamatan Lamba Leda Kabupaten Manggarai Timur Ditinjau Dari Peraturan Menteri Dalam Negeri Nomor 18 Tahun 2018 Tentang Lembaga Kemasyarakatan Desa Dan Lembaga Adat Desa - Melin, Yunita; Monteiro, Yosef M; Ermalinda, Jenny (Law Faculty, Nusa Cendana University, 2025)
This study aims to examine the role of customary institutions in the development of Tengku Lawar Village and Lamba Keli Village located in Lamba Leda District, East Manggarai Regency, with the legal basis of the Minister of Home Affairs Regulation Number 18 of 2018. In this study, an empirical legal approach was used with data collection through interviews, observations, and document studies. The results of the study indicate that customary institutions have a very important role in several aspects, namely: (1) maintaining and preserving cultural identity through a series of traditional ceremonies such as Penti, Kalok, and Wagal; (2) protecting the customary rights of the community through the tente teno system; (3) encouraging the implementation of deliberation and consensus, or what is known as lonto leok; (4) resolving disputes related to customs; and (5) regulating community life in accordance with applicable customary law. However, in carrying out these functions, customary institutions face several obstacles, including limited understanding of the law, low quality of human resources (especially those with basic education), and minimal allocation of funds after the COVID-19 pandemic. This study highlights the need for collaboration between village governments and traditional institutions to integrate local wisdom with modern development.